Development of a Fatty Liver Model by Restricted Feeding of Lactating Sheep - Yang, Wei; Li, Xiaobing; Liu, Guowen; Zhang, Hongyou; Chen, Yuanyuan; Xia, Cheng; Xu, Chuang (Acta Scientiae Veterinariae, 2018)
Background: As a frequent subclinical disease, fatty liver disease (FLD) is associated with a severe negative energy balance (NEB) during the early lactation period, and usually cause of economic loss to dairy farmers. Liver biopsy is the gold standard for the assessment of FLD. However, as an invasive procedure, liver biopsy has several limitations and such procedures are not readily available to dairy farmers. To further evaluate FLD in dairy cows, a FLD model of lactating sheep was developed by simulation of the state of negative energy balance (NEB). Materials, Methods & Results: Fourteen pregnancy thin-tail ewes were divided into control group (CG, n = 4), non-lamb restrained feeding group (NRG, n = 4) and single birth restrained feeding group (SRG, n = 6). After lambing, NRG and SRG ewe were received a feed restrained diet for 16 days. Liver biopsies and blood was collected on days 1, 4, 7, 10, 13, and 16, and biochemical parameters were analyzed. With restricted feeding and lactation administration, ewes in SRG showed increased liver fat concentrations (LFC) from days 4 post-administration and severe LFC was detected at day 13. Compared with CG, SRG sheep showed significant lower concentration of serum glucose (Glu) from days 7-13 and higher non-esterified fatty acid (NEFA) from days 4-16, β-hydroxybutyric acid (BHBA) from days 4-16, triglyceride from days 4-16, low-density lipoprotein cholesterol from days 4-16, lactate dehydrogenase (LDH) from days 13-16, aspartate aminotransferase (AST) at days 16. While, ewes in NRG showed normal LFC levels, and high concentration of serum Glu and insulin from days 4-16 were detected than CG and SRG ewes. With restricted feeding, ewes in NRG and SRG showed significant low level of revised quantitative insulin sensitivity check index from days 4-16 and high level of liver total cholesterol (TC) at day 16. Liver pathological characteristics showed LFC of NEB sheep was first detected around the liver portal area. Discussion: In this study, a model of FLD in lactating thin-tail sheep was developed by restricted feeding. Serum glucose concentrations were sharply decreased in SRG sheep，that was due to the large energy requirements for lactation and low energy provided by a restricted diet. While non-lactating NRG sheep demonstrated lower fat mobilization, which was considered to contribute to the high concentrations of serum glucose, as compared to SRG sheep. Meanwhile, in a state of NEB, oxaloacetic acid, which is generated by glycolysis and glycogenic amino acids, tends to be used for gluconeogenesis, that a generous amount of NEFA is incompletely oxidized to generate ketone body in SRG sheep, which is a major component of BHBA. Liver TC concentrations were significantly higher in NRG sheep than those in the SRG sheep, while liver triglyceride was significantly lower. The high level of liver TC in NRG sheep was considered to induce removal of triglyceride from the liver in the form of VLDL. Compared with CG sheep, although higher levels of liver TC were detected in SRG sheep on postpartum day 16, these levels were considered too low to induce significant depletion of triglycerides from the liver. In this study, the increase in serum AST and LDH was considered to cause by oxidative stress in mitochondria, and LDH concentrations was considered more sensitively than AST for LFC caused by NEB. Liver pathological characteristics showed that FLD caused by NEB had a major impact on reduced LFC, although no significant liver fibrosis was detected. While different from FLD caused by high-fat diet, TG was first accumulates around the hepatic lobules and LFC of NEB sheep was first detected around the liver portal area. It was considered that high concentrations of NEFA are prioritized for oxygenation in the liver portal area, which results in triglyceride accumulation.